Tributação sobre serviços digitais prestados a usuário no exterior - Mortati, Ananda Arruda Campos Rudi (2025)
In light of significant changes in the global economic landscape driven by the Digital Economy and the development of new technologies, this study aims to systematically analyze the taxation on the provision of services, with a focus on services provided to users abroad. The study addresses the issues and distortions that generate litigation. It involves an analysis of the guidelines and debates from the Organization for Economic Cooperation and Development (OECD) to determine whether these guidelines will be observed, when applicable, in Brazilian legislation. This study also seeks to identify the impacts on Brazilian tax litigation concerning topics related to the digital economy and the changes introduced by Constitutional Amendment No. 132/2023, along with its regulations and the challenges faced